CRITICAL THEORY OF FRANKFURT SCHOOL: APPLICATION IN EDUCATION AND THE DEVELOPMENT OF ISLAMIC CRITICAL THEORY - Anuhgra, Yudha Okta; Arif, Mahmud; Rahmadhani, Saszlin (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
The present study aims to provide a comprehensive examination of the Frankfurt School’s Critical Theory, encompassing its historical origins, subsequent development, and the application of its values within educational contexts and the evolution of Islamic Critical Theory. Employing a qualitative research methodology, data for this article were obtained through an extensive review of literature, including books, scholarly journals, and other pertinent documents concerning the Frankfurt School’s Critical Theory. Data analysis was performed using content analysis techniques. The findings indicate that the Frankfurt School’s Critical Theory remains a significant philosophical movement, persisting not only in Western academic discourse but also among Muslim philosophers. Despite its limited familiarity in Indonesia, there is potential for the adaptation of aspects and values of the Frankfurt School’s Critical Theory in the educational process. This adaptation could be achieved through the implementation of critical pedagogy, aimed at fostering understanding and sensitivity to promote change. Additionally, the integration of critical religious education could serve to transform it into critical Islamic religious education, thereby challenging the prevailing stigma that often pits Islam and the West against each other in the educational field. Furthermore, it is imperative to acknowledge the significant opportunity for academics and philosophers to continue developing the concept of Islamic Critical Theory, a field that currently has minimal references. Critical theory has the potential to contribute to the development of Islamic scholarship, as evidenced by the Qur’an’s emphasis on critical thinking in the pursuit of knowledge.